Optimización del proceso de elaboración de láminas de cartón con parafina en el ondulado en la Empresa Papelera Nacional S.A. del cantón Marcelino Maridueña, año 2014 - Barrera Cordero, Carlos Iván (2015)
The present work is based on the study to optimize the process of production of sheets of carton with paraffin in waved of the company National Wastebasket S.A. located in the canton Marcelino Maridueña, the above mentioned study will be on the basis of the information obtained in the year 2014. For this investigation it has been necessary to possess several technologies and methods of investigation as the survey, which is the one that has helped us to obtain the precise information to do the check of the exposed hypothesis hereinafter. One of the tools that it will help us to be able to develop and to investigate the raised topic, is the accomplishment of a format of control, which contains all the technical characteristics of the process in different contours. This format, it is realized on the basis of the needs and requirements of the process to take a record during his development, helping to evaluate the times and quantities of raw material. During the study there has been finalized that is necessary the suitable use of the inputs that intervene in the process, which will help to reach the raised aim, announcing to the personnel the changes that have to be realized in the area. It is necessary that the whole personnel is to so much and earring of the process, doing a periodic control that helps to verify what appears in the offer to optimize the mentioned process. Key words: Process, Sheets of carton, paraffin